2016
DOI: 10.5455/bcp.20161123044657
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation in Schizophrenia: A Critical Review and The Future

Abstract: Neuroinflammation in schizophrenia: a critical review and the future Schizophrenia is a serious mental illness that affects approximately 1% of the population worldwide, with positive, negative and cognitive dysfunctions and a significant deterioration in psychosocial functioning. Interactions between genetic predisposition and environmental stressors at the early stages of life, and subsequently a molecular level neurodegeneration process are important in the development of schizophrenia. Current approaches s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Monitoring activated microglia is of great interest to assess disease severity and progression (3) as well as therapeutic efficacy of antiinflammatory drugs. Several recent lines of evidence support that neuroinflammation plays an important role in schizophrenia (4,5). For the past decades, the firstgeneration radiotracer 11 C-PK11195 has been widely used as a biomarker but suffered from low brain extraction and thus poor signal-to-noise ratio (6)(7)(8).…”
mentioning
confidence: 99%
“…Monitoring activated microglia is of great interest to assess disease severity and progression (3) as well as therapeutic efficacy of antiinflammatory drugs. Several recent lines of evidence support that neuroinflammation plays an important role in schizophrenia (4,5). For the past decades, the firstgeneration radiotracer 11 C-PK11195 has been widely used as a biomarker but suffered from low brain extraction and thus poor signal-to-noise ratio (6)(7)(8).…”
mentioning
confidence: 99%
“…The earliest approaches in the biology of dopamine receptor and its targeting, signaling cascades and possible opportunities for target therapy with minimum side effect has been investigated [4][5][6]. Structural and biochemical studies have shown the subtypes of dopamine receptors in one of two groups of receptors D1 and D1b / D5 have a very high homology in domains of their membrane width and similarly retain membrane width sequences among the receptors D2, D3, D4 [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…2 Similarly, in the past 7 years, data supporting an immune-mediated cause in schizophrenia have also increased substantially. 3 This advocates that research is now entering a new era of immunopsychiatric investigations that will profoundly change the understanding of brain disorders, in which immune impairments will be now acknowledged as potential underlying mechanisms of altered behavioral manifestations.…”
Section: Introductionmentioning
confidence: 99%